A.R BASWEDAN DAN PAI: POTRET NASIONALISME WARGA KETURUNAN PERSPEKTIF SOSIOPOLITIK HISTORIS - Nafilah Abdullah (Jurnal Sosiologi Agama, 2017)
In this article, the authors review about A.R. Baswedan and his movement through the Arab Party of Indonesia (PAI). A.R Baswedan is an Arab descendant known as the pioneer of independence of the Republic of Indonesia. The author through historical socio-political studies found that A.R Baswedan is an example of Arabic descent who counter Arabism and views between the Arab descendants and the descendants of indigenous Indonesians are the same or equal and the same fate. They both have one nationality, Indonesia. This fusion attitude in the Indonesian citizenship and nationality equation is evident in its movement within the PAI.Keywords: A.R. Baswedan, Biography, and Thought (PAI)